2013
DOI: 10.1111/are.12208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial substrate and night-time aeration on the water quality inMacrobrachium amazonicum(Heller 1862) pond culture

Abstract: The effects of artificial substrate and night-time aeration on the culture of Macrobrachium amazonicum were evaluated in 12 ponds stocked with 45 prawns m À2 . A completely randomized design in 2 9 2 factorial scheme with three replicates was used. The combination of factors resulted in four treatments: with substrate and aeration (SA), with substrate and without aeration (SWA), without substrate and with aeration (WSA) and without substrate and aeration (WSWA). The presence of substrate in SA and SWA treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…Asaduzzaman et al (2008) also showed that the total ammonia-nitrogen concentration in the treatment pond can be controlled at a lower level than that in the control pond after the addition of a substrate, implying that the substrate supports the growth of nitrifying bacteria and algae, which in turn reduces total ammonia-nitrogen and NO 2 − -N levels. In addition, our results also showed that in most cases, the concentration of TN and TP in pond water could be reduced by the presence of artificial substrata; nitrite, ammonia-nitrogen, and nitrate also showed a similar trend, especially for grass carp cultured at a high culture density (D40 and D50), in accordance with the results of previous studies (Azim et al, 2002;Asaduzzaman et al, 2008;Kumar et al, 2015;Henares et al, 2015). These results thus showed that water quality might be very important for the growth of aquaculture species, suggesting that water quality control should be strictly maintained during this process.…”
Section: Discussionsupporting
confidence: 92%
“…Asaduzzaman et al (2008) also showed that the total ammonia-nitrogen concentration in the treatment pond can be controlled at a lower level than that in the control pond after the addition of a substrate, implying that the substrate supports the growth of nitrifying bacteria and algae, which in turn reduces total ammonia-nitrogen and NO 2 − -N levels. In addition, our results also showed that in most cases, the concentration of TN and TP in pond water could be reduced by the presence of artificial substrata; nitrite, ammonia-nitrogen, and nitrate also showed a similar trend, especially for grass carp cultured at a high culture density (D40 and D50), in accordance with the results of previous studies (Azim et al, 2002;Asaduzzaman et al, 2008;Kumar et al, 2015;Henares et al, 2015). These results thus showed that water quality might be very important for the growth of aquaculture species, suggesting that water quality control should be strictly maintained during this process.…”
Section: Discussionsupporting
confidence: 92%
“…In benthonic rearing systems, the aerators reduce the water column stratification, which improves the bottom habitat for animal growth (Rogers & Fast 1988). An increase in the nitrogen concentration in water benefits the phytoplankton development in carp polyculture (Catla catla, Labeo rohita, Labeo fimbriatus and Puntius sarana) tanks (Pawar et al 2009) and the periphyton growth in Macrobrachium amazonicum ponds (Henares et al 2013). Autotrophic organisms assimilate inorganic compounds; in addition to improving the water quality, they can result in better productivity and decrease the nitrogen and phosphorus levels in the effluent (Bratvold & Browdy 2001;Asaduzzaman et al 2009).…”
Section: Rearing Systems and Management Practicesmentioning
confidence: 99%
“…) and the periphyton growth in Macrobrachium amazonicum ponds (Henares et al . ). Autotrophic organisms assimilate inorganic compounds; in addition to improving the water quality, they can result in better productivity and decrease the nitrogen and phosphorus levels in the effluent (Bratvold & Browdy ; Asaduzzaman et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The substrates are natural screens (e.g., bamboo, branches) or artificial screens (e.g., screens, nets) installed inside the culture ponds to increase the production area; especially, benthic organisms reduce heterogeneous growth and agonistic behavior like well and improve animal welfare (Karplus and Sagi 2010). The addition of substrates allows the growth of periphyton, which absorbs nitrogen and phosphorus, enhancing water quality, and provides food to the shrimps (Tidwell & Bratvold 2005;Henares et al 2015). In this study, no substrate was used in the shrimp culture tanks that have limited space.…”
Section: Performance Shrimpmentioning
confidence: 99%